Synthesis of ZnO nanostructures with different morphologies on biochar support for photocatalytic degradation of organic dye - maryam Fayazi (Journal of Water and Environmental Nanotechnology)
In the present study, different morphologies (viz., spherical and nanoroad) of zinc oxide (ZnO) were successfully deposited on the biochar support material via a simple hydrothermal approach. The biochar utilized in this research was obtained through the pyrolysis process of pistachio residues. Characterization of the prepared ZnO/biochr nanocomposites was carried out using FT-IR, XRD, DRS, EDS and SEM analyses. DRS data analysis revealed that the band gap energies of the fabricated nanocomposites were measured to be 2.98 eV and 3.08 eV for the spherical ZnO/biochar and nanoroad ZnO/biochar, respectively. Under visible light irradiations, the prepared photocatalysts were assessed for their photocatalytic abilities in degradation of methylene blue (MB) dye. The degradation of MB on ZnO/biochar catalysts demonstrates a strong correlation with a pseudo-first-order kinetic model. Besides, the suggested photocatalyst substance indicated good reusability, retaining its performance for at least five cycles. The utilization of low expense biochar support in conjunction with nanosized ZnO nanostructures presents a promising idea to achieve efficient photocatalysts for the degradation of organic pollutants.